Odpowiedź :
Odpowiedź:
[tex]a) \: \frac{2}{5} + 4 \frac{3}{7} + \frac{3}{5} = \frac{2}{5} + \frac{3}{5} + 4 \frac{3}{7} = 1 +4 \frac{3}{7} = 5 \frac{3}{7} [/tex]
[tex]b) \: 4 \frac{2}{3} + 2 \frac{3}{7} + \frac{1}{3} + \frac{4}{7} = 4\frac{2}{3} + \frac{1}{3} + 2 \frac{3}{7} + \frac{4}{7} = 5 + 3 = 8[/tex]
[tex]c) \: 3 \frac{2}{7} + 1 \frac{1}{3} + 4 \frac{3}{7} + 2 \frac{1}{6} + \frac{1}{2} = 3 \frac{2}{7} + 4 \frac{3}{7} + 1 \frac{2}{6} + 2 \frac{1}{6} + \frac{3}{6} = 7 \frac{5}{7} + 4 = 11 \frac{5}{7} [/tex]
[tex]d) \: 2 \frac{3}{5} + \frac{2}{9} + 3 \frac{1}{2} + \frac{1}{3} + \frac{7}{10} = 2 \frac{6}{10} + 3 \frac{5}{10} + \frac{7}{10} + \frac{2}{9} + \frac{3}{9} = 6 \frac{4}{5} + \frac{5}{9} = 6 \frac{36}{45} + \frac{25}{45} = 7 \frac{16}{45} [/tex]
Mam nadzieję, że pomogłam :)
a)
²/₅ + 4 ³/₇ + ³/₅ = ²/₅ + ³/₅ + 4 ³/₇ = ⁵/₅ + 4 ³/₇ = 1 + 4 ³/₇ = 5 ³/₇
b)
4 ²/₃ + 2 ³/₇ + ¹/₃ + ⁴/₇ = 4 ²/₃ + ¹/₃ + 2 ³/₇ + ⁴/₇ = 4 ³/₃ + 2 ⁷/₇ = 5 + 3 = 8
c)
3 ²/₇ + 1 ¹/₃ + 4 ³/₇ + 2 ¹/₆ + ¹/₂ = 3 ²/₇ + 4 ³/₇ + 2 ¹/₆ + 1 ¹/₃ + ¹/₂ =
= 7 ⁵/₇ + 2 ¹/₆ + 1 ²/₆ + ³/₆ = 7 ⁵/₇ + 3 ⁶/₆ = 7 ⁵/₇ + 4 = 11 ⁵/₇
d)
2 ³/₅ + ²/₉ + 3 ¹/₂ + ¹/₃ + ⁷/₁₀ = 2 ³/₅ + 3 ¹/₂ + ⁷/₁₀ + ²/₉ + ¹/₃ =
= 2 ⁶/₁₀ + 3 ⁵/₁₀ + ⁷/₁₀ + ²/₉ + ³/₉ = 5 ¹⁸/₁₀ + ⁵/₉ = 6 ⁸/₁₀ + ⁵/₉ =
= 6 ⁴/₅ + ⁵/₉ = 6 ³⁶/₄₅ + ²⁵/₄₅ = 6 ⁶¹/₄₅ = 7 ¹⁶/₄₅